A practical microwatt-meter for electrical energy measurement in programmable devices. (November 2018) - Al-Shorman, Mohammad Y; Al-Kofahi, Majd M; Al-Kofahi, Osameh M
Background: In this work, an accurate low-cost power microwatt-meter is designed, built, and tested. This microwatt-meter is found to be capable of measuring power consumption in a wide range of devices and sensors, such as nodes in wireless sensor networks, microcontrollers in Internet of Things devices, and Field Programmable Gate Arrays. Methods: The paper examines the usage of the microwatt-meter for the measurement of power consumption in digital devices as they execute program instructions, ranging from a low-level single step (instruction) in an assembly program to a high-level sophisticated program or system. Results: The results obtained showed that the microwatt-meter is highly accurate. It can measure the energy consumed by any of the devices/programs/instructions in a digital system with accuracy levels ranging between 0.5% and 2.5% (depending on the application). Conclusion: The accuracy of the microwatt-meter is validated using the fundamental conservation of energy law and a comparison with multimeter current measurements is presented.